Valores humanos e jeitinho brasileiro: uma análise da transmissão de pais para filhos - Sousa, Marília Mendes Moreira de (2020)
The Brazilian way is a national way found to solve aversive or difficult situations in daily life. It is known that the phenomenon can be transmitted through socialization of parenting educational practices. There is a lack of studies about the period in which this behavior starts to be developed and used as a way to solve problems. Therefore, it is clear that the transmission of values from parents to children, beyond the Brazilian way, is still subject to further studies. The general objective is to verify to what extent the parenting relations influence the learning of the Brazilian way on children through transmission of values. To answer, the research has been divided in two studies, the first being about the adaptation of an instrument of Brazilian way to children, and the second one evaluating the Brazilian way and the transmission of values on children and their providers observing the levels of correspondence between the dyad. There were a sample of 131 children on study 1 and 101 dyads on study 2. Since the last one, 94 have been answered by parents-children, which 77.2% were mothers. The participants expressed their assent and consent through the Informed Consent Form. The instruments used for both researches were: The Questionnaire about the Brazilian way – Individual version, Questionnaire of child and adult Basic Values, infant and adult Biosociodemographic Questionnaire and Questionnaire about the Brazilian way – Infant version, made by the author. On study 1, descriptive statistics were performed analysis of the main components, factor analysis of the main axes, internal consistency, KMO index and the Sphericity test of Barlett. For the number of components to be extracted, Catell, Kaiser, Parallel Analysis and Hull criteria were used. In the results, the QJB-INF was adapted and validated, suggesting two factors defined as creativity and antisocial. In study 2, descriptive statistics were performed Pearson correlation, means comparison test, simple and multiple linear regression, in addition of intraclass data analysis. As result, it was found that the Brazilian way transmitted through parenting socialization in which adult factors are predictive from the children variables. In addition, the human values are tangled to the Brazilian way, explaining the construct of children creativity and antisocial behavior.